Severe neuro-Behcet's disease treated with a combination of immunosuppressives and a TNF-inhibitor - (:unkn) unknown (PUBLISAUDE-EDICOES MEDICAS LDA, 2016)
Behcet's disease (BD) is a multisystem inflammatory disorder characterized by recurrent oral and genital ulcers, skin lesions and uveitis. The nervous system involvement of BD, neuro-Behcet's disease (NBD), is one of the important causes of mortality of the disease. Herein, we present a 29-year-old male with parenchymal NBD who has progressed rapidly and was managed with an uncommon aggressive immunosuppressive combination therapy. The patient first presented six years ago with vertigo and difficulty in talking and walking. On examination, he had oral ulcers, acneiform lesions on the torso, genital ulcer scar, dysarthria, and ataxia. Along with the magnetic resonance imaging (MRI) findings, the patient was diagnosed as NBD. After pulse methylprednisolone (1g/day, 3 days) and 8 courses of lg/month iv cyclophosphamide therapy, he was put on azathioprine and oral methylprednisolone. On the 4th year of the maintenance therapy, he was admitted with NBD relapse which was treated with 3 days of iv lg pulse methylprednisolone. One year after the last relapse, the patient voluntarily stopped medications and presented with global aphasia, right hemihy-poesthesia and quadriparesis. MRI findings were suggestive of NBD relapse. After exclusion of infection, pulse methylprednisolone was started but no improvement was observed. Considering the severity of the NBD, the patient was put on methylprednisolone (1mg/kg/day), iv cylophosphamide (lg) and adalimumab 40 mg/14 days subcutaneously with appropriate tuberculosis prophylaxis. Neurological examination and MRI findings after 4 weeks showed dramatic improvement however patient developed pulmonary tuberculosis. Methylprednisolone dose was decreased (0.5mg/kg/day) and quadruple antituberculosis therapy was started. Patient was discharged with 5/5 muscle strength in extremities without any respiratory symptoms 2 months after the first presentation. Prompt introduction of immunosuppressive therapy is crucial in NBD. Although combination of TNF inhibitors and cyclophosphamide is a rare therapeutic approach, it may be life-saving. However a higher awareness is required for opportunistic infections.
Keywords: TNF inhibitors; Neurologic involvement; neuro-Behcet's disease; ADALIMUMAB; RISK; INFECTION; EFFICACY; PATIENT